Deciphering the safeguarding role of cysteine residues in p53 against H2O2-induced oxidation using high-resolution native mass spectrometry - Manuel David Peris-Díaz; Artur Krężel; Perdita Barran (Communications Chemistry)
Abstract The transcription factor p53 is exquisitely sensitive and selective to a broad variety of cellular environments. Several studies have reported that oxidative stress weakens the p53-DNA binding affinity for certain promoters depending on the oxidation mechanism. Despite this body of work, the precise mechanisms by which the physiologically relevant DNA-p53 tetramer complex senses cellular stresses caused by H2O2 are still unknown. Here, we employed native mass spectrometry (MS) and ion mobility (IM)-MS coupled to chemical labelling and H2O2-induced oxidation to examine the mechanism of redox regulation of the p53-p21 complex. Our approach has found that two reactive cysteines in p53 protect against H2O2-induced oxidation by forming reversible sulfenates.